Game-Based Learning Media to Improve Students' Understanding in Chemistry Learning - Farah Erika; Odi Aksha; Devi Nawang Ariningtyas; Iftatun Qolbiah; Aisha Nur Safrida (Hydrogen: Jurnal Kependidikan Kimia, 2023)
One of the supporting factors for the success of a lesson is an increase in students' understanding of the material being taught. The use of learning media can help students understand the material easily. This literature review discusses the use of game-based learning media to increase high school students' understanding of chemistry. This study uses the narrative literature review method, by analyzing several literature sources related to game-based learning media. The results of the study show that game-based learning media can encourage students to learn actively anywhere and anytime so that they can increase students' cognitive abilities in understanding chemical material. Game-based learning media can be applied to all grade 10 and 11 chemistry materials at the senior high school (SMA) level.